2016
DOI: 10.4102/ojvr.v83i1.1002
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiological survey and risk factors associated with bovine brucellosis among slaughtered cattle in Nigeria

Abstract: Bovine brucellosis is endemic in Nigeria; however, limited data exist on nationwide studies and risk factors associated with the disease. Using a cross-sectional sero-epidemiological survey, we determined the prevalence of and risk factors for brucellosis in slaughtered cattle in three geographical regions of Nigeria. Serum samples from randomly selected unvaccinated cattle slaughtered over a period of 3 years (between December 2010 and September 2013) from northern, southern and south-western Nigeria were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 28 publications
6
15
2
4
Order By: Relevance
“…The only factor associated with Brucella infection in food animals observed in this study was that related to the breed of the animals especially in goats probably due to genetic variation which is an important factor in conferring resistance or tolerance to certain types to diseases [ 17 ]. This finding is in contrast to the reports of Mai et al that brucellosis in animals is not breed specific [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only factor associated with Brucella infection in food animals observed in this study was that related to the breed of the animals especially in goats probably due to genetic variation which is an important factor in conferring resistance or tolerance to certain types to diseases [ 17 ]. This finding is in contrast to the reports of Mai et al that brucellosis in animals is not breed specific [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Predisposing factors reported by other studies for seropositivity to Brucella infection in cattle are breed and sex of animals [ 17 ]. Other studies reported that sex of the animals was a risk factor for seropositivity to Brucella infection [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brucellosis in cattle is usually caused by B. abortus , in sheep and goats by B. melitensis , and in swine by B. suis [ 2 ]. However, bovine brucellosis has occasionally been caused by Brucella melitensis and Brucella suis in some instances where mixed farming is practiced [ 2 , 3 ], characterized by late term abortion, infertility, and reduced milk production [ 1 , 2 , 4 ]. Human brucellosis is mainly associated with B. abortus , B. melitensis , and B. suis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of public awareness and poor or low income communities have been largely associated with the neglect of the disease [ 13 ]. The persistence and wide prevalence ranges of bovine brucellosis in sub-Sahara Africa are influenced by several factors associated with disease transmission between herds, factors influencing the maintenance and spread of infection within herds, purchase of infected cattle from livestock market for replacement or upgrading, nature of the animal production system, demographic factors, regulatory issues, climate, deforestation, and wildlife interaction [ 3 , 7 , 14 , 15 ]. Although poorly implemented, the control of major zoonoses in Cameroon is mainly through the regulation of animal movement and postmortem examination of carcasses [ 12 ] such that appropriate preventive measures and planning of effective control programs cannot be achieved.…”
Section: Introductionmentioning
confidence: 99%